2023
DOI: 10.1039/d3cp00253e
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prediction of 11B NMR chemical shift of BODIPYs via machine learning

Abstract: In this article, we present the results of developing a model based on RFR machine learning method using the ISIDA fragment descriptors for predicting the 11B NMR chemical shift of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…More specifically, in Bruker NMR systems, having two spectra, for example, 1 H and, e.g., 14 N or 19 F, after referencing the first (in Method A or, much better, using Method B), the second spectrum is usually standardized indirectly [73] with respect to the 1 H frequency using the xiref referencing macro implemented in TopSpin software. Importantly, it avoids the widespread, but now not-recommended, use of primary external standards, namely 15% BF 3 •OEt 2 in CDCl 3 , neat CH 3 NO 2 , neat CFCl 3 , and 85% H 3 PO 4 , respectively [12,[77][78][79], which is usually less accurate and sometimes very dangerous. In fact, it can be assumed that the death of an academic chemist as a result of exposure to liquid Me 2 Hg (external reference for 199 Hg NMR spectroscopy) accelerated the introduction of this universal procedure at the expense of using the highly problematic Method E [80][81][82].…”
Section: Methods For 1 H/ 13 C Chemical Shift Referencementioning
confidence: 99%
“…More specifically, in Bruker NMR systems, having two spectra, for example, 1 H and, e.g., 14 N or 19 F, after referencing the first (in Method A or, much better, using Method B), the second spectrum is usually standardized indirectly [73] with respect to the 1 H frequency using the xiref referencing macro implemented in TopSpin software. Importantly, it avoids the widespread, but now not-recommended, use of primary external standards, namely 15% BF 3 •OEt 2 in CDCl 3 , neat CH 3 NO 2 , neat CFCl 3 , and 85% H 3 PO 4 , respectively [12,[77][78][79], which is usually less accurate and sometimes very dangerous. In fact, it can be assumed that the death of an academic chemist as a result of exposure to liquid Me 2 Hg (external reference for 199 Hg NMR spectroscopy) accelerated the introduction of this universal procedure at the expense of using the highly problematic Method E [80][81][82].…”
Section: Methods For 1 H/ 13 C Chemical Shift Referencementioning
confidence: 99%
“…In this context, it is essential to know the properties and possible use of emerging compounds, so that they can be of benefit for different applications. It should be noted that recent studies have implemented a machine learning algorithm to predict 11 B NMR chemical shifts in emerging organic compounds, adding techniques and methodology for spectral studies [28]. In this sense, it is important to have a detailed knowledge of the physical and chemical characteristics of the molecule, as well as its electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al found that isotropic 11 B NMR chemical shifts from the borosilicate minerals correlated with the local geometric parameters of the tetrahedrally coordinated B sites [8]. Ksenofontov et al provide a convenient tool and database that we collected for all researchers, that allows us to predict the 11 B NMR chemical shift of boron-containing dyes [9]. Reto Horst et al describe NMR spectroscopy as the Swiss army knife of drug discovery [10].…”
Section: Introductionmentioning
confidence: 99%